Analisis Pengelolaan Dana Zakat untuk Mendorong Peningkatan Ekonomi Masyarakat Kecamatan Barumun (BAZNAS Kabupaten Padang Lawas) - Melyati Melyati; Junda Harahap; Aminah Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Zakat is the fourth pillar of Islam that must be carried out by a Muslim who has been able to achieve the nisab that has been determined and the time of ownership has reached 1 haul. The legal basis regarding zakat is in the Al-Quran surah Al-Baqarah verse 110. The collection of zakat funds is carried out to help people in need, especially mustahik people who receive zakat. Through this research, it is hoped that it will be known how BAZNAS in Padang Lawas district carries out its duties as a zakat management institution and the extent to which BAZNAS has contributed to improving the economy of the Islamic community in the region. The results of this research can be an important input for BAZNAS and other related parties to continue to improve the effectiveness of zakat fund management and community economic empowerment. The results of this study indicate that the management of zakat funds in BAZNAS Padang Lawas district. It has 2 types of distribution of zakat funds, namely consumptive zakat and productive zakat where productive zakat has an economic program where BAZNAS provides business capital to Muslim communities who submit application proposals to the Padang Lawas district BAZNAS office to help improve the community's economy but lack the skills of mustahiq who receive zakat capital in developing their business so that they are given training for those who are really interested in running a business. In this way, it is hoped that it will reduce the failure of mustahik to receive business capital.